THE ROLE OF LINGUISTICS AND LOCAL WISDOM ON KNOWING HARMONY BETWEEN RELIGIONS AT TANA TORAJA - Riyantino Yudistira; Muta'allim Muta'allim; Nurcaya Nurcaya; Julhadi Julhadi; Petrus Pattiasina Jacob Pattiasina (IAIN Ponorogo, 2022)
AbstractHarmony between religious communities is everyone's dream, but living in a plural society is very difficult to avoid conflict. Therefore, this research is presented in order to provide views related to the concept of knitting harmony between religious communities through linguistics and local wisdom. This study aims to identify and describe the role of linguistic concepts and local wisdom in knitting inter-religious harmony at Tana Toraja land with a phenomenological approach. This research is a qualitative research with observation and interview methods. Data obtained from interviews with Tana Toraja speakers by voice recording and field note-taking. In addition, the researcher was assisted by the experience of the informants by using the reflective-introspective method. The results of the study show that (1) the linguistic concept can prevent misunderstandings, violence, fanaticism, be sensitive and be able to make inter-religious people aware of the grace of diversity at Tana Toraja land so as to create humanist communication. (2) the role of local wisdom can build solidarity, togetherness, harmonious relations, and religious awareness in a plural society so as to create peaceful social relations. The role of linguisitics and local wisdom can make Tana Toraja societies have harmony relation with others without see the status (race, ethnic, religion, and so on). AbstrakKerukunan antar umat beragama merupakan dambaan setiap orang, namun hidup dalam masyarakat majemuk sangat sulit untuk menghindari konflik. Oleh karena itu, penelitian ini dihadirkan untuk memberikan pandangan terkait konsep merajut kerukunan antar umat beragama melalui linguistik dan kearifan lokal. Penelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan peran konsep linguistik dan kearifan lokal dalam merajut kerukunan antar umat beragama di tanah Tana Toraja dengan pendekatan fenomenologis. Penelitian ini merupakan penelitian kualitatif dengan metode observasi dan wawancara. Data diperoleh melalui wawancara dengan masyarakat Tana Toraja dilengkapai dengan teknik rekam dan catat. Selain itu, peneliti dibantu oleh pengalaman informan dengan menggunakan metode reflektif-introspektif. Hasil penelitian menunjukkan bahwa (1) konsep kebahasaan dapat mencegah terjadinya kesalahpahaman, kekerasan, fanatisme, peka dan mampu menyadarkan umat antar umat beragama akan anugerah keberagaman di tanah Tana Toraja sehingga tercipta komunikasi yang humanis. (2) peran kearifan lokal dapat membangun solidaritas, kebersamaan, hubungan yang harmonis, dan kesadaran beragama dalam masyarakat majemuk sehingga tercipta hubungan sosial yang damai. Peran linguistik dan kearifan lokal dapat membuat masyarakat Tana Toraja memiliki hubungan yang harmonis dengan orang lain tanpa melihat status (ras, suku, agama, dan sebagainya).